(untitled) (Bangladesh Journal of Nuclear Agriculture, 2026)
The study aimed to assess the shelf life and quality of red and white fleshed dragon fruit under various postharvest treatments at the Horticulture Division of Bangladesh Institute of Nuclear Agriculture, Mymensingh during the period from November 2023 to January 2024. The experiment was laid out in completely randomized design included two factors such as Factor A: Variety (V1 = red fleshed, V2 = white fleshed) and Factor B: Postharvest treatments (T1: control, T2: 12.5µm LDPE bag, T3: gamma irradiation @ 1000 Gy + LDPE bag, T4: 3% NaOCl dip (10 minutes) + LDPE bag, T5: 3% CaCl2 dip (10 minutes) + LDPE bag, T6: storing at 4°C + LDPE bag). The parameters studied were weight loss, firmness, titratable acidity (TA), total soluble solids (TSS), disease severity and shelf life. Red fleshed fruit showed superior firmness (2.22), TA (0.33%) and TSS (13.80% Brix). Whereas, white fleshed fruit demonstrated lower weight loss (6.01%) and disease severity (3.72) at the 11th day of storage. White fleshed fruit also had a slightly longer shelf life (15.44 days). Among treatments, T6 significantly extended shelf life to 51.88 days. In combined effects, V1T6 showed better TA (0.37%) and TSS (12.93% Brix), while V2T6 minimized weight loss (0.84%). The longest shelf life (52.50 days) was observed in V2T6. The findings would greatly contribute in reducing postharvest loss of dragon fruits and maintain their quality during marketing at ambient condition. Bangladesh J. Nuclear Agric, 39(2): 63-76, 2025